1986
DOI: 10.1148/radiology.158.1.3940374
|View full text |Cite
|
Sign up to set email alerts
|

Cervical internal carotid artery dissecting hemorrhage: diagnosis using MR.

Abstract: Two men underwent high-resolution magnetic resonance (MR) imaging of the internal carotid artery (ICA) 12 and 16 days after spontaneous dissection of this vessel. One underwent follow-up MR imaging 7 weeks later. T1-weighted images were obtained in both cases, and T2-weighted images were obtained in one patient. In both cases, the MR findings corresponded to the angiographic abnormalities. On both the T1- and T2-weighted images, there was a hyperintense lesion expanding the wall and narrowing the lumen of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(47 citation statements)
references
References 0 publications
2
43
0
2
Order By: Relevance
“…Evolution of the hematoma within a vessel wall has not been extensively studied, but it is possible that high T1 signal intensity may not be present during the early acute period. 15,21,22 T2-weighted sequences (with or without fat saturation) may add sensitivity for the diagnosis of dissection in the setting of absent or equivocal findings on T1-weighted imaging, to evaluate hyperacute blood or wall edema.…”
Section: Discussionmentioning
confidence: 99%
“…Evolution of the hematoma within a vessel wall has not been extensively studied, but it is possible that high T1 signal intensity may not be present during the early acute period. 15,21,22 T2-weighted sequences (with or without fat saturation) may add sensitivity for the diagnosis of dissection in the setting of absent or equivocal findings on T1-weighted imaging, to evaluate hyperacute blood or wall edema.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] However, acquisition of 2D T1-weighted images is time-consuming and has limited longitudinal coverage. Recently, the 3D black-blood T1-weighted imaging technique has been used to detect IMH in patients with arterial dissection.…”
Section: Agreement Between 3d Snap and Multisequence 3d Mr Imagingmentioning
confidence: 99%
“…Previous studies reported that the signal of IMH will change with time on MR vessel wall imaging. 13,22 To evaluate the usefulness of SNAP imaging in the characterization of CCAD, further prospective studies with larger sample sizes are warranted.…”
Section: Agreement Between 3d Snap and Multisequence 3d Mr Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…- 29 Finally, in the near future, the combination of MR angiography of the carotid artery including the distal cervical and intracranial segments with the assessment of characteristic flow dynamics by duplex Doppler and the display of the vascular wall hemorrhage on MR scans will probably limit the use of conventional angiography to a few selected cases.…”
mentioning
confidence: 99%